Perancangan Sistem Informasi Penjualan Spare Part Kendaraan di CV Berkah Otomotif Motor Berbasis Web - Andriawan, Deden; Windiarti, Ika Safitri; Prabowo, Agung (Universitas Muhammadiyah Tangerang, 2025)
The development of information technology has brought significant changes to the trade sector, with e-commerce as an alternative that allows transactions to be conducted online without the limitations of space and time. This research aims to design a web-based spare parts sales information system for CV Berkah Otomotif Motor to improve efficiency and ease of access for customers. The research methods used are observation, interviews, and documentation to collect relevant data. The system is developed using the prototype method, which allows users to interact with the system from the early stages and provide iterative feedback. Unified Modeling Language (UML) is used as a design tool to model the system in a structured manner. System testing is conducted using black-box testing, which focuses on testing functionality without looking at the source code, to ensure that each function works as expected. The results of this research show that the designed system can help customers obtain information about the availability of spare parts and allow online ordering, thereby improving comfort and transaction efficiency. With this system in place, CV Berkah Otomotif Motor is expected to expand its market reach and enhance its competitiveness in the digital era.